ANALYSIS OF COMPETITIVENESS OF ENTERPRISES IN THE RESTAURANT SERVICES MARKET - Yudina, O. I.; Nebaba, N. O.; Sabirov, O. V.; Saihak, Ye. L.; Altunin, K. O. (Systems and Technologies, 2024)
The article conducts a comparative analysis and evaluation of the market positions of restaurant enterprises to identify key areas for their development and ways to increase their competitiveness in the food service market. The main goal of this article is to analyze the competitiveness and assess the development potential of restaurant enterprises in the Dnipropetrovsk region, justifying ways to improve their market positions. The study analyzes the current restaurant services market and identifies key development directions, including the growth of demand for healthy food, technological progress, the development of gastronomic tourism, social media, and information technologies. A comparative graph-analytical method for determining competitiveness and ranking restaurant enterprises is formulated, consisting of operations such as forming criteria parameters and establishing their weights, selecting competitors, determining ranking characteristics, calculating competitiveness indicators and overall enterprise ranking, identifying leaders and outsiders, building a competitiveness matrix and zone, and determining the radius of the leaders’ circle. Based on the results of the graph-analytical analysis, the indicators for evaluating the potential of the studied enterprises in the restaurant services market of the Dnipropetrovsk region were calculated according to defined criteria parameters, as well as their level of competitiveness. Using the obtained indicators, a matrix and a graph of the competitive positions of the establishments were built. By determining the placement range of each food enterprise in the competitive field zone, their positions were characterized as follows: the "Silver" restaurant is in the zone of untapped potential; the "Magnum" restaurant is closest to the leader in the attack waiting zone; the "Oasis" restaurant is in the leaders’ zone, and the "Kvitan" restaurant is in the outsiders’ zone. Based on the evaluation results of the "Kvitan" enterprise, proposals for improving its activities and strengthening its competitive positions were formulated, including: improving the atmosphere, increasing comfort and service quality, enhancing staff qualifications, and greening the restaurant’s territory.